Revitalizing a community language: Livonian and other community languages - Christopher Moseley (Eesti ja Soome-ugri Keeleteaduse Ajakiri, 2016)
The present paper compares efforts to revive the spoken use of two European languages which have fallen into disuse: Cornish, spoken in the southwest of England, and Livonian in Latvia. Different approaches have been taken in encouraging heritage learners to use the languages again, but there are points in common, and each has something to learn from the other. The work of the Cornish Language Partnership in organizing and encouraging Cornish learners is compared with the courses run by the branch of the Livonian Association in Kolka, Kurzeme.